Sustainable Construction Building Performance Simulation and Asset and Maintenance Management - Delgado, João M.P.Q (Building Pathology and Rehabilitation, 2016)
This book presents a collection of recent research works that highlight best practice solutions, case studies and practical advice on the implementation of sustainable construction techniques. It includes a set of new developments in the field of building performance simulation, building sustainability assessment, sustainable management, asset and maintenance management and service-life prediction. Accordingly, the book will appeal to a broad readership of professionals, scientists, students, practitioners, lecturers and other interested parties.